The Increasing potential competition, value added and supply chain management of pandan leaves agricultural products in Nakhon Pathom province. - Pimonrattnakan, Sudarat (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research aims to elevate ability the increasing potential competition, value-added and supply chain management of pandan leaves agricultural products in Nakhon Pathom province. Using qualitative research, phenomenological Approach. The key informants were 25 farmers or the president of community enterprise, tools such as in-depth interviews and non-engaging observations, together with studying data from documents. Data collection and data analysis with content analysis methods. The findings showed that the guidelines for ability the Increasing potential competition , Value-added and supplt chain management of pandan leaves agricultural products that will affect farmers Performance. 1) The potential competition is important and affects the supply chain management of local wisdom in pandan leaves agricultural products. 2) The value-added is important and affects the supply chain management of local wisdom in pandan leaves agricultural products. 3) The supply chain management is important and affects the farmers Performance. By upgrading product development by processing pandan products according to local wisdom by developing products including distribution channels of pandan products according to local wisdom by using the application of the pandan leaf page And there are model farmers in supply chain management in pandan agricultural products of Nakhon Pathom province. In which the benefits of supply chain mangement and creativity of local wisdom to farmers Article history : Received 31 July 2021 Revised 18 October 2021 Accepted 20 October 2021 SIMILARITY INDEX = 2.95 %